'Laetitia' plums stored in controlled atmosphere and active modified atmosphere packing with ethylene management Manejo do etileno em ameixas 'Laetitia' armazenadas sob atmosferas controlada e modificada ativa1 - Correa T.R.* (2011)
The objective of this study was to evaluate the effect of controlled atmosphere (CA) and active modified atmosphere packing (MAP) [LDPE film (40 μm), with two perforations (diameter = 1.0 mm) with ethylene management, on quality preservation of 'Laetitia' plums. The cold storage (60 days at 0.5±0.1oC) treatments evaluated were: stored atmosphere (SA; 21.0 kPa O2 + <0.03 kPa CO2); MAP; MAP + low ethylene (LE); CA; and CA + treatment with 1-MCP (1,0 μL L-1). The partial pressures of O2 + CO2 (kPa) were 1.0 + 1.0and 2.5 + <0.1, in CA and MAP, respectively. Fruits stored in CA, regardless of ethylene removal, showed ripening delay compared to fruit in CS. However, the best preservation of flesh texture and titratable acidity was achieved in CA + 1-MCP. The incidences of decay, skin cracking and flesh browning were not different between treatments. Fruits stored in MAP + LE and CA + 1-MCP had lower internal darkening and higher acceptability for color and taste compared to fruit stored in SA.